Can Debt Crises Be Self-Fulfilling? - Chamon, Marcos (IMF Working Papers; Working Paper ;, 2004)
Several papers argue that debt crises can be the result of self-fulfilling expectations that no one will lend to a country. I show this type of coordination failure can be eliminated by a combination of state-contingent securities and a mechanism that allows investors to promise to lend only if enough other investors do so as well. This suggests that runs on the debt of a single borrower (such as the government) can be eliminated, and that self-fulfilling features are more plausible when articulated in a context in which externalities among many decentralized borrowers allow for economy-wide debt runs to occur.